Development of Deaf Adults with Intellectual Disability in a Therapeutic Living Community. (21st April 2020) - Fellinger, Johannes; Linzner, Doris; Holzinger, Daniel; Dall, Magdalena; Fellinger, Maria; Fogler, Jason
Abstract: People with intellectual disabilities who are deaf face obstacles participating in social environments that do not take into account their need for accessible visual communication. In the present case series, we describe the development of the adaptive skills profiles of eight participants in a fully inclusive therapeutic living community, designed specifically for people with developmental disabilities who are deaf and focused on supporting communication, social relationships, conflict resolution, and work satisfaction. Adaptive skills ratings collected at enrollment and twelve years later suggest increases in social awareness and community living, whereas personal care and homemaking showed relatively little change.